Literasi Keuangan Dosen di Palembang: Faktor Pendapatan, Pendidikan, dan Kepemilikan Produk Keuangan - Fransiska Soejono; Anastasia Sri Mendari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2019)
This study aims to measure the level of financial literacy of lecturers in Palembang based on their income, education, and ownership of financial produk. The study sample was 153 respondents. Data were analyzed using descriptive analysis techniques and crosstabulation. Distribution of questionnaires with closed questions is done to collect data. The financial literacy index is divided into two groups, namely basic financial literacy and advanced financial literacy. The calculation for each variable is done using the simple weight method. The results showed that on average the basic financial literacy index of high income lecturers was included in the high category, while the advanced financial literacy index average was included in the low category for lecturers with income categories of less than or equal to nine million rupiah. The basic financial literacy index of lecturers with an average S1 education background is in the low category, while the advanced financial literacy index of lecturers with educational backgrounds S1, S2, and S3 is in the low category. The basic financial literacy index of lecturers of state and private universities is more dominant in the high category, while the advanced financial literacy index of the dominant state and private higher education lecturers is in the low category. The basic financial literacy index of lecturers from the Faculty of Economics / Business is more dominant in the high category, while lecturers from non-economic / business faculties are more dominant in the low category. Lecturers with a basic financial literacy index that is low, moderate and high in addition to having a savings account also have several financial products that are not too high risk such as government securities and mutual funds. Lecturers with a low advanced financial literacy index are more dominant in having bank and non-bank savings as well as insurance and credit cards.